The effect of femoral head size on volumetric wear rate following total hip joint replacement surgery - Jason Rahmadi Ruslie (Intisari Sains Medis, 2019)
Background: Numerous data records that the number of total hip joint replacement is increasing in many parts of the world which also indicates an increase demand for total hip joint replacement and revision surgery. The purpose of this paper is to review the literature regarding the size of femoral head and its relation to the volumetric wear rate of the polyethylene lining of the hip’s acetabular component.Methods: A systematic literature search performed to identify relevant publications for this review in five databases: University of Melbourne Science, Medline/ Pubmed, Cochrane Library, and Ebsco. The search was completed on 6 October 2012 and again on 24 October 2012. The following keywords and phrases were used: total hip joint replacement, femoral head size, wear, polyethylene and arthroplasty.Results: The six studies are all prospective cohort studies with a follow-up time ranging between three to ten years at the minimum. One study conducted by Hammerberg et al. did not mention the minimum length of their follow up however they include a mean follow up period which is 3.6 years. Two studies did not mention the number of patients they are following up. Every other studies mention how many participants included in their study, but these two studies mention how many hips undergo the total hip joint replacement surgery. The number of patients mentioned in the studies vary from the minimum of 42 patients up until 200 patients. The number of hips in each study ranged from 45 hips to 385 hips.Conclusion: This review concludes that the use of larger femoral head size hastens the wear rate of the polyethylene lining of the acetabulum component.